Renal Amyloidosis - Muhammad, Noor; R., Ghaffar; Y., Khan; Ullah, Rafi; Jamil, Shahid (Journal of Postgraduate Medical Institute, 2011)
Amyloidosis is not a single disease entity rather it is a family of different diseases having multisystem involvement. There are several causes of amyloidosis having different frequency in the world. In the west amyloidosis is mainly AL type and hence affects elderly population. Secondary amyloidosis (AA) is rare and commonly due to infmammatory bowel diseases or rheumatoid arthritis. we conducted a cross sectional hospital based study at the Departmetn of Medicine HMC Peshawar 1998 - 2001. In our setup post TB ronchiectasis was the commonest cause of amyloidosis and most of our patients are young. Males were more commonly affected as compared to females AL amyloidosis was very rare. A larger community based study is needed to explore the epidemiology of amyloidosis as it affects the bread earning population of our society.